The Effect of Combined Tensile-Torsional Loading Path on the Stress/Strain States of Thin-Walled Circular Tubes - Yue Gao; Fei Shao; Qian Xu; Linyue Bai; Qingna Ma; Mei Shen; Lixiang He; Ming Chen (Advances in Civil Engineering)
In this paper, an elastoplastic analysis model of thin-walled circular tubes under the combined action of axial force and torque is discussed. Based on the von Mises yield criterion and the assumption of isotropic linear hardening, the methods of stress path and strain path loading are analyzed to study the effect of combined tensile-torsional loading path on thin-walled circular tubes. A finite element model is used to analyze the loading path effect on thin-walled circular tubes. A series of tensile and torsional tests are also carried out on 304 stainless steel thin-walled circular tubes using a universal testing machine. In addition, the consistency of the selected material with the von Mises yield criterion, the assumption of isotropic linear hardening, and other classical elastoplastic mechanics are verified. The theoretical calculation results, the numerical analysis results, and the experimental test results are analyzed and compared. The “primary effect” influenced by the stress path and the “recency effect” affected by the strain path are proved, and their application prospects are discussed. The influence of tensile-torsional loading path on the final stress and strain states of thin-walled circular tubes after entering the plastic deformation stage is concretely demonstrated, facilitating the understanding of the principles of the aforementioned two effects. The investigation for a general principle concerning the effect of loading history on the mechanical behavior of engineering materials, based on the classical plastic mechanics, has an important theoretical significance. It is of great theoretical importance for advancements in plastic yield theory and the establishment of more accurate loading conditions suitable for specific materials in engineering practice.